Manajemen Mutu dalam Meningkatkan Akreditasi MTs. Swasta Al – Amin Batu Tunggal - Makmur Syukri; Retno Pringadi; Sri Rezeqi Rafiqah Wardhah Manurung; Uswatun Hasanah; Siti Rahma ismiatun (Journal on Education, 2023)
The purpose of this study is to describe madrasa quality management, implementation, quality management to improve accreditation and quality management barriers in improving MTs accreditation. Private Al-Amin Batu Tunggal. This type of research uses a qualitative research type where the data collection techniques are observation, interviews and documentation. The method in this study uses a qualitative research method, namely an approach that produces written or spoken words from people who are used as respondents. Quality management of education in MTs. Private Al-Amin Batu Tunggal If seen from the naked eye this Madrasa has not managed the quality management contained in it, caused by a lack of care and the lack of good learning facilities so that school management has not run as expected. In addition, the available land is limited so that the facilities and facilities are also limited. Quality management research in improving accreditation in MTs. Private Al-Amin Batu Tunggal is going well. After doing quality management research in MTs. Private Al-Amin Batu Tunggal is quite good, it can be seen from the work program of the madrasah principal and the collaboration and student achievements, but the madrasah accreditation is still C. The madrasah principal also forms a team that works together and has qualifications in their respective fields so that they are able to complete the National Standard Education well.